Nitric oxide-an endogenous inhibitor of gastric acid secretion in isolated human gastric glands - Ericson Ann-Charlott (BMC Gastroenterology, 2004)
Abstract Background Endothelial nitric oxide synthase (eNOS) has previously been detected in the glandular part of the human gastric mucosa. Furthermore, nitric oxide (NO) has been shown to influence gastric secretion in various animal models. The present study was conducted to investigate the influence of exogenously and endogenously derived NO on histamine- and cAMP-stimulated gastric acid secretion in isolated human oxyntic glands. Methods Oxyntic glands were isolated from human gastric biopsies and were subsequently pre-treated with NO donors and nitric oxide synthase inhibitors and then exposed to histamine or dibutyryl-cAMP (db-cAMP). The secretory response of the glands was determined as accumulation of [14C]aminopyrine. Results The histamine- or db-cAMP-induced acid secretion was attenuated by L-arginine, a known source of endogenous NO, and also by the NO-donors sodium nitroprusside (SNP) and S-nitroso-N-acetyl-penicillamine (SNAP). Pre-treatment with either of the NOS inhibitors NG-nitro-L-arginine methyl ester (L-NAME) or NG-nitro-L-arginine (L-NNA) enhanced the secretory response. Conclusion Our results show that NO inhibits gastric acid secretion in isolated human gastric glands, and that there is endogenous formation of NO within the glandular epithelium in the vicinity of the parietal cells.